2001
DOI: 10.1002/ajmg.10111
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset of Parkinson disease and apolipoprotein E genotypes

Abstract: Several lines of evidence suggest that the variable age at onset of Parkinson disease (PD) is likely influenced by genes. The apolipoprotein E (APOE) gene is associated with onset of Alzheimer disease, and possibly other neurodegenerative disorders. APOE has been investigated in relation to onset of PD, but results have been inconsistent. The aim of the present study was to determine if APOE genotypes are associated with onset age of PD, using a patient population large enough to assure sufficient power. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 35 publications
2
36
1
Order By: Relevance
“…The association of APOE ε4 with earlier age at onset of ALS without SOD1 gene mutations suggests that an impaired brain regenerative capacity conferred by the ε4 allele may interact with ALS-causing genetic and/or environmental factors to make the disease present earlier, although there is no detectable influence of APOE variants on disease risk. Similar findings have been reported in PD and Pick's disease [21,22]. Moreover, much of the association of APOE ε4 with sporadic, but not necessarily familial, AD is caused by the earlier age at onset in ε4 carriers [23][24][25].…”
Section: Discussionsupporting
confidence: 72%
“…The association of APOE ε4 with earlier age at onset of ALS without SOD1 gene mutations suggests that an impaired brain regenerative capacity conferred by the ε4 allele may interact with ALS-causing genetic and/or environmental factors to make the disease present earlier, although there is no detectable influence of APOE variants on disease risk. Similar findings have been reported in PD and Pick's disease [21,22]. Moreover, much of the association of APOE ε4 with sporadic, but not necessarily familial, AD is caused by the earlier age at onset in ε4 carriers [23][24][25].…”
Section: Discussionsupporting
confidence: 72%
“…Average age at onset was 2.2 years earlier in ε4-carriers than non-ε4-carriers (56.6 ± 12.3 vs. 58.8 ± 12.1, p=0.0002). A modest but significant association between ε4 and age at onset of PD has been noted previously [Pankratz et al, 2006; Zareparsi et al, 2002]. …”
Section: Resultsmentioning
confidence: 63%
“…13 However, a later study using a relatively large sample size (521 unrelated Caucasian PD patients) showed that individuals with APOE-34 or APOE-44 genotypes, not APOE-23 carriers, have significantly earlier AAO than those with the APOE-33 genotype. 14 Significant association has also been found between the APOE-4 allele and PD patients with dementia. 11 Finally, the APOE-24 genotype was shown to associate with PD in a small Chinese sample (69 PD cases and 160 controls).…”
mentioning
confidence: 95%